Phytosociological study of Andrew's field and the Tsaba-Tsaba nature reserve, Bredasdorp distict, Western Cape - Bredenkamp, George J. (University of Pretoria, 2013)
Dissertation (MSc(Botany))--University of Pretoria, 2005.